Fatores de atraso da alta hospitalar em enfermarias de clínica médica de dois hospitais públicos na cidade de Belo Horizonte, Minas Gerais - Soraia Aparecida da Silva (2011)
Introduction: The delay in hospital discharges decreases hospital bed availability, increases healthcare costs and the number of adverse events related to prolonged hospitalization, such as hospital infections, embolic complications and depression. Identification of the causes of delay in hospital discharge is the first step to implement measures to reduce this delay and increase the efficiency in the use of hospital beds. Objectives: To assess the adequacy of hospital stay and identify the reasons for delay in hospital discharge in a sample of patients hospitalized in the medical clinic at two teaching hospitals in Belo Horizonte, Minas Gerais in the period from January to March 2010. To also identify the specialties associated with a higher rate of delay in hospital discharges and quantify the delay in the discharge of these patients. Methods: Retrospective study that analyzed 217 medical records in Hospital das Clínicas da UFMG (HC) and 185 medical records in hospital Odilon Behrens (HOB) with the use of the instrument Appropriateness Evaluation Protocol (AEP) that has been validated in several countries. The difference between the date of hospital discharge and the date that hospital stay was considered inadequate by AEP was considered the period of delay in hospital discharge. In patients who experienced this delay the reasons for its occurrence were analyzed using the instrument proposed by Selker et al. (1989). Results: In HC 60% of patients had delayed hospital discharge which corresponds to 23% of occupancy rate. The average delay was 4.4 days. The main reasons for delay was waiting for laboratory testing (31.6%) or to release the reports of examinations (23.2%) and those related to medical responsibility (37.4%), among them the difficulty in achieve consultations, delay to discuss the case and in making clinical decisions. In 20% of patients the delay in hospital discharge was due to a single reason, 19% of patients had two reasons and 12% had 4-6 reasons for delay in hospital discharge. In HOB 58% of patients had delayed hospital discharge which corresponds to 28% of occupancy rate. The reasons that contributed most to the delay were similar to those observed in HC, but waiting for laboratory testing played a major role. In HOB 17.8% of patients had one reason and 9.8% of patients had 4 to 5 reasons for delay in hospital discharges. The orthopedic medical specialty was the largest contributor to increasing the length of delay in hospital discharge due to delay in responding to consultations. Conclusion: We observed a high percentage of delayed hospital discharges in HC and HOB, with significant impact on the average hospital stay and occupancy rate. This delay is mainly caused by difficulties in making clinical decisions and the completion and release of results of diagnostic tests. Changes in the work process in laboratory and imaging services and in the work flow of consultations and clinical decision making can lead to significant reduction of delay in hospital discharges.